The Effect Of Candlenut (Aleurites moluccanus) Concentration On Moisture Content, Ash Content, Color, And Sensory Evaluation Of Powdered Broth From Bones And Heads Of Mackerel (Rastrelliger sp) - Dewi Sartika; Hani Tiara Anjasia; Sussi Astuti; Sri Hidayati (Jurnal Media Akuakultur Indonesia, 2025)
Fish-based powder broth generally has a fishy odor caused by the high content of trimethylamine (TMA) compounds in fish. To reduce this unpleasant smell, candlenut is added as an antioxidant. This study aims to determine the effect of candlenut concentration on the moisture content, ash content, color, and sensory characteristics of powder broth made from the bones and heads of mackerel. The study used a Completely Randomized Design (CRD) with further analysis using the Honestly Significant Difference (HSD) test at a 5% level. The research was conducted in two stages: product preparation and analysis, which included chemical tests (moisture and ash content), physical tests (color), and sensory evaluation. The results showed that the addition of candlenut had a significant effect on all tested parameters. Formulation K4 yielded the best results, with a moisture content of 5.80%, ash content of 3.42%, and color values of L 75.84, a 2.48, and b* 19.91. The sensory scores for this formulation were 4.36 for taste, 5.16 for aroma, 5.26 for color, and 4.54 for texture. These findings indicate that the addition of candlenut can improve the physical and sensory quality of fish-based powder broth and reduce the undesirable fishy odor